2015
DOI: 10.1039/c5tc01345c
|View full text |Cite
|
Sign up to set email alerts
|

Not your familiar two dimensional transition metal disulfide: structural and electronic properties of the PdS2monolayer

Abstract: By means of density functional theory (DFT) computations, we theoretically investigated a novel two-dimensional (2D) transition metal disulfide (TMD), namely PdS 2 monolayer. Distinguished from other 2D TMDs which adopt the ordinary 2H or 1T configuration, PdS 2 monolayer presents rather unique structural properties: each Pd atom binds to four S atoms in the same plane, and two neighboring S atoms can form a covalent S−S bond. The hybrid HSE06 DFT computations demonstrated that PdS 2 monolayer is semiconductin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
120
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(141 citation statements)
references
References 62 publications
16
120
2
3
Order By: Relevance
“…The monolayer band gaps from the HSE calculations, 2.50 eV (PtS 2 ), 2.00 eV (PtSe 2 ), and 1.20 eV (PtTe 2 ) (see Fig. S1 in Supplemental material), are in very good agreement with optical gap [44,54]. is covered by hydrogen atoms and the other one (X-2) remains unsaturated.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…The monolayer band gaps from the HSE calculations, 2.50 eV (PtS 2 ), 2.00 eV (PtSe 2 ), and 1.20 eV (PtTe 2 ) (see Fig. S1 in Supplemental material), are in very good agreement with optical gap [44,54]. is covered by hydrogen atoms and the other one (X-2) remains unsaturated.…”
Section: Resultssupporting
confidence: 63%
“…[41] has sparked renewed interest in Pt (and Pd) chalcogenides [42][43][44]. Like the corresponding bulk materials, the monolayers are nonmagnetic semiconductors, which leads to the question whether and how these film can be made magnetic.…”
Section: Introductionmentioning
confidence: 99%
“…[21] Importantly, the layer binding energy of PdSe 2 is 190 meV per atom, [21] which is relatively higher than graphite (≈35 meV per atom), [22] h-BN (52 meV per atom), [23] and black phosphorous (40 meV per atom) [23] but few studies are reported about obtaining monolayer PdSe 2 by mechanical exfoliation. [21,23,26] In the few layered structure, Se vacancies break the symmetry and induce large structural distortion and as a result PdSe 2 adopts pentagonal rings with the vertices in a slightly asymmetrical puckered structure that is different from other TMDs. [21,23,26] In the few layered structure, Se vacancies break the symmetry and induce large structural distortion and as a result PdSe 2 adopts pentagonal rings with the vertices in a slightly asymmetrical puckered structure that is different from other TMDs.…”
Section: Doi: 101002/adma201904251mentioning
confidence: 99%
“…[16][17][18][19][20] Among them, palladium diselenide (PdSe 2 ) is attracting attention due to its interesting electronic properties and atomic structure. [21] Importantly, the layer binding energy of PdSe 2 is 190 meV per atom, [21] which is relatively higher than graphite (≈35 meV per atom), [22] h-BN (52 meV per atom), [23] and black phosphorous (40 meV per atom) [23] but few studies are reported about obtaining monolayer PdSe 2 by mechanical exfoliation. [24,25] In contrast to the frequently reported hexagonal phases in TMDs, PdSe 2 has a unique structure, Figure 1a.…”
mentioning
confidence: 99%
“…Wang et al found PdS 2 monolayer presents rather unique structural properties: each Pd atom binds to four S atoms in the same plane, and two neighboring S atoms can form a covalent S-S bond, which is distinguished from other 2D transition metal disulfides. 119 The PdS 2 monolayer is semiconducting with Overview wires.wiley.com/compmolsci an indirect band gap of 1.60 eV, and has a rather large hole and electron mobilities. Yang et al found two kinds of 2D SiS materials that are energetically and thermally stable.…”
Section: Other Materialsmentioning
confidence: 99%